Extrusion of Poly(ether imide) Foams Using Pressurized CO2: Effects of Imposition of Supercritical Conditions and Nanosilica Modifiers - Aktas, Seda; Gevgilili, Halil; Kucuk, Ilknur; Sunol, Aydin; Kalyon, Dilhan M. (WILEY, 2014)
Foams of an engineering plastic, poly(ether imide), were extruded using a single screw extruder employing pressurized CO2 as the blowing agent. The porosity, pore size distributions, and the density of the foams were especially affected by the pressure drop, the pressure loss rate, and temperature at the die. Significant increases in porosity and pore size and corresponding decreases in density were observed when the pressure imposed on CO2 became greater than the critical pressure values of CO2 (i.e., the temperature was always greater than the critical temperature of the CO2 in the extruder and the die). The viscoelastic material functions of the extruded foams depended especially on the density of the foam, with the elastic modulus increasing with density. The incorporation of nanosilica particles in the 0.08-0.6% by weight range increased only the density of the foam and did not provide any benefits in controlling of the nucleation rate and the pore size distribution, presumably due to their poor dispersibility and agglomerated state in the single screw extruder. (C) 2013 Society of Plastics Engineers
Keywords: CARBON-DIOXIDE; DIE GEOMETRY; MICROSTRUCTURE DEVELOPMENT; DENSITY DISTRIBUTIONS; CELL NUCLEATION; TUBE FLOW; POLYSTYRENE; POLYPROPYLENE; EXPANSION; RHEOLOGY; Engineering; Polymer Science